THE ANALYSIS OF PHASE COMPOSITION OF BINARY ALLOYS MOLYBDENUM AND TUNGSTEN ON THE BASIS OF INTERATOMIC INTERACTION COMPONENTS - Dorohan, T. E. (Science and Transport Progress, 2010)
The article is devoted to the problem of phase composition formation in molybdenum and tungsten electrodeposited alloys as well as to the comparison of data concerning the structure of alloys obtained by means of electrocrystallization and through high-rate quenching of melt. The work develops the trend of predicting the structure and properties of alloys as a result of analysis of general regularities of non-equilibrium crystallizations. The new technique for estimation of conditions and intermolecular interaction of components in electrodeposited iron’s group metals alloys with tungsten and molybdenum is offered. The electrodeposited alloys Мо, W have similar laws as from the point of view of electrochemical kinetics of their allocation as phase structure. It opens opportunities to obtaining alloys with the beforehand given structure and properties and has importance for the solving a problem of creating new materials.